Assessing Elite Athletes using PROMIS Tools: The STEALTH Project (Student Athlete Health Assessment). Issue 4 (16th October 2019) - Challa, Shanthan; Lakey, Eric; Smith, Kenneth; Holliday, Marissa; Vest, Jonah; Gattas, Carina; Hunt, Kenneth
Category: Sports, Outcomes Introduction/Purpose: Injuries are a major part of elite sports and patient-reported outcomes tools (PROs) are becoming commonplace for the assessment of injury and treatment outcomes. The National Institutes of Health (NIH) Patient-Reported Outcomes Measurement Information System (PROMIS) is a validated set of assessment tools with increasing popularity. The PROMIS metrics utilize computerized adaptive testing (CAT) to capture health status measurements through individualized assessments, with minimal user burden, and without the loss of precision or content validity. The purpose of this study was to evaluate elite athletes using PROMIS scores and assess the impact of injury on those scores in order to gain insight into how participation and injury can impact the health of NCAA Division 1 athletes participating in a variety of sports. Methods: Over a six-month period, athletes from 11 sports at a single Division 1 Athletics program were recruited to participate in longitudinal prospective data collection using four PROMIS CAT scales/domains: Pain Interference (PI), Physical Function (PF), Depression, and Ability to Participate in Social Roles and Activities (PSRA). Using REDCap (Research Electronic Data Capture), athletes completed an assesment that included the PROMIS tools prior to participation in their respective sport's season for the 2018-2019 academic year and following the completion of their season. Athletes suffering a season-ending injury were asked to complete the PROMIS survey within a week following the injury. De-identified data was analyzed using Student's T-test. PROMIS outcome measures were analyzed using linear mixed model regression. A p-value of < 0.05 was considered statistically significant. Results: A total of 315 pre-season surveys were collected and of those 139 post-season surveys have been completed at this point in the academic year. PF, Depression and PSRA scores were significantly different in athletes than in the general age-matched population. PI scores were similar to the normal population. The distribution of PI and PF scores were significantly different pre and post-season with a difference in means of 2.2 and -3.2 respectively (p<.01). No significant difference was observed in the Depression and PSRA scores at the end of the season. A total of 23 significant injuries were reported up to this point in the season, resulting in a significant change from both pre-season scores and post-season in uninjured controls (Figure 1). Conclusion: We found significantly worse PI and PF scores after a full season compared to preseason, suggesting that athletic participation alone impacts the athlete's overall function and condition. Season-altering injuries resulted in clinically significant differences in all four domains, suggesting that injuries greatly affect athletes not only physically, but mentally and socially. These data indicate that consideration should be given to pre-season PROMIS surveys for individual athletes to ensure that subsequent scores are properly interpreted. Additional study will elucidate the impact of specific sports and injuries, providing data to physicians, trainers, and coaches to inform treatment and return to sport protocols.